Factors Impacting The Final-Year Students’ Perceived Stress During Pandemic: SBM-ITB Students' Thesis Progress (Journal of Business and Management, 2022)
Some studies in Indonesia have proven that many students are stressed and even experience severe stress while writing a thesis. During the COVID-19 pandemic, students' stress while writing a thesis is exacerbated due to the changing learning system. However, no study at the SBM-ITB explores students' stress levels while writing a thesis, especially during the COVID-19 pandemic. The leading cause of the stress they experience has also never been proven. In this study, the researcher investigates the SBM-ITB final-year students' stress levels while writing a thesis during this pandemic and identifies the source of their stress (stressors). Using 67 samples through the PSS-10 questionnaire, most SBM-ITB final-year students reported being under moderate to severe stress. Semi-structured interviews were conducted with the 10 respondents that were at least under moderate stress. By using thematic analysis, the interview data results show four stressors significantly affect students' stress: Relationship, Time Management/Workload, Financial, and Academic. Through the FGD, the researcher validated the interview data results and discovered Time Management/ Workload is the leading stressor affecting students' stress. Four stressors adversely impact the students, leading them to delay their thesis progress. The students claimed that the pandemic situations influenced all stressors they experienced.